Determinants of circumcision and willingness to be circumcised by Rwandan men, 2010 - Gasasira, Rwego A.; Sarker, Malabika (BMC public health, 2012)
Male Circumcision (MC) has been recommended as one of the preventive measures against sexual HIV transmission by the World Health Organization (WHO). Rwanda has adopted MC as recommended but the country is a non-traditionally circumcising society. The objective was to explore knowledge and perception of Rwandan men on Male Circumcision (MC) and to determine the factors associated with the willingness to be circumcised and to circumcise their sons.